SalinLikas a collborative Resource Recovery and Waste collection facility promoting circular economy and public education on proper waste management practices in Quezon City - Ables, Aiyana Danica A.
The Philippines faces a waste management crisis marked by ineffective systems, weak enforcement, lack of standardized operations, and limited public education. In Quezon City, the country's most populous urban area, these challenges are particularly pronounced. This study proposes a collaborative resource recovery and waste collection facility grounded in circular economy principles to address these issues. It aims to reduce waste generation, encourage public participation through incentives, and foster learning opportunities about waste management. A mixed-methods approach was employed. Descriptive research provided quantitative insights into waste patterns through surveys, while phenomenological research captured qualitative perspectives from stakeholders. Exploratory research adapted international precedents to the local Philippine context. Findings were integrated into architectural and operational solutions suited to the local setting. The facility is designed to include spaces for waste collection, sorting, and mechanical processing of six waste types: clothing and textiles, plastics, paper, glass, metal and electronics. Public education and collaboration are central, with initiatives like a trash-to-cash incentive system and spaces for educational activities. The architectural design emphasized efficiency, accessibility, and a community-centered approach, avoiding industrial aesthetics to blend seamlessly into urban environments. This study highlights the potential to transform waste management in the Philippines by combining education, community collaboration, and advanced processes. The proposed facility serves as a model for sustainable urban waste management, addressing environmental challenges while promoting innovative design and public engagement.